Homologs of the Xenopus developmental gene DG42 are present in zebrafish and mouse and are involved in the synthesis of Nod-like chitin oligosaccharides during early embryogenesis. - Semino, C E (1996)
The Xenopus developmental gene DG42 is expressed during early embryonic development, between the midblastula and neurulation stages. The deduced protein sequence of Xenopus DG42 shows similarity to Rhizobium Nod C, Streptococcus Has A, and fungal chitin synthases. Previously, we found that the DG42 protein made in an in vitro transcription/translation system catalyzed synthesis of an array of chitin oligosaccharides. Here we show that cell extracts from early Xenopus and zebrafish embryos also synthesize chitooligosaccharides. cDNA fragments homologous to DG42 from zebrafish and mouse were also cloned and sequenced. Expression of these homologs was similar to that described for Xenopus based on Northern and Western blot analysis. The Xenopus anti-DG42 antibody recognized a 63-kDa protein in extracts from zebrafish embryos that followed a similar developmental expression pattern to that previously described for Xenopus. The chitin oligosaccharide synthase activity found in extracts was inactivated by a specific DG42 antibody; synthesis of hyaluronic acid (HA) was not affected under the conditions tested. Other experiments demonstrate that expression of DG42 under plasmid control in mouse 3T3 cells gives rise to chitooligosaccharide synthase activity without an increase in HA synthase level. A possible relationship between our results and those of other investigators, which show stimulation of HA synthesis by DG42 in mammalian cell culture systems, is provided by structural analyses to be published elsewhere that suggest that chitin oligosaccharides are present at the reducing ends of HA chains. Since in at least one vertebrate system hyaluronic acid formation can be inhibited by a pure chitinase, it seems possible that chitin oligosaccharides serve as primers for hyaluronic acid synthesis.